Nutritional evaluation of the lipid fraction of Iberian red deer (Cervus elaphus hispanicus) tenderloin. - Quaresma, M a G; Trigo-Rodrigues, I; Alves, S P; Martins, S I V; Barreto, a S; Bessa, R J B (Meat science, 2012)
The meat lipid fraction of psoas major muscle from 20 adult (10 males and 10 females) feral Iberian red deer (Cervus elaphus hispanicus) was characterized by quantification of total fat, total cholesterol, vitamin E and fatty acid (FA) composition, including detailed trans octadecenoate isomers and conjugated linoleic acid (CLA) isomeric profile. The total lipid content revealed a very lean meat (0.99 g/100g of meat), with total cholesterol content averaging 55.6 mg/100g of muscle. The FA profile displayed a very high PUFA level for ruminant meat (30.2g/100g FA). The 18:2 cis-9,trans-11 content was fairly low (0.26% of total FA) compared with other ruminant meats. The comparison of stags and hinds showed more similarities than differences. Nevertheless, hinds displayed superior contents of α-tocopherol and trans MUFA and a better n-6/n-3 ratio than stags.
Keywords: cervus elaphus hispanicus; Cholesterol; CLA; Fatty acid profile; meat quality; Vitamin E

Fatty acid composition, conjugated linoleic acid isomers and cholesterol in beef from crossbred bullocks intensively produced and from Alentejana purebred bullocks reared according to Carnalentejana-PDO specifications. - Alfaia, C M M; Ribeiro, V S S; Lourenço, M R a; Quaresma, M a G; Martins, S I V; Portugal, a P V; Fontes, C M G a; Bessa, R J B; Castro, M L F; Prates, J a M (Meat science, 2006)
The purpose of this study was to characterise and compare the nutritional value of Portuguese Carnalentejana-PDO beef, obtained from Alentejana purebred bullocks reared in a semi-extensive system, with the meat from Alentejana×Charolais crossbred bullocks produced in a conventional intensive concentrate-based system. In addition, seasonal changes in Carnalentejana-PDO beef quality were assessed, by analysing meat samples from animals slaughtered in early autumn and late spring. The results showed that beef-PDO has different intramuscular fat characteristics in comparison with meat from crossbred bullocks fed intensively with concentrate. However, the finishing period of Alentejana purebred bullocks with concentrate seems to attenuate most of the typical grass-fed characteristics of meat fat. Nevertheless, from a human nutrition perspective, Carnalentejana-PDO beef seems to be healthier than that from intensively reared animals since it has a lower n-6/n-3 ratio, although always above the recommended guidelines for human diet, and higher proportions of c9,t11 conjugated linoleic acid (CLA) isomer and total CLA relative to saturated fatty acids plus total cholesterol (CLA/SFA+CHR). Furthermore, no seasonal variation in the nutritional quality of beef-PDO was apparent. Taken together, the data indicate that Carnalentejana-PDO beef is of greater nutritional value than intensively produced beef from crossbred bullocks throughout the year.
Keywords: Beef; Cholesterol; CLA isomers; fatty acids; meat quality; Production systems